2015
DOI: 10.1002/ange.201505641
|View full text |Cite
|
Sign up to set email alerts
|

Proteome‐Wide Profiling of Targets of Cysteine reactive Small Molecules by Using Ethynyl Benziodoxolone Reagents

Abstract: In this study,wepresent ahighly efficient method for proteomic profiling of cysteine residues in complex proteomes and in living cells.O ur method is based on alkynylation of cysteines in complex proteomes using a" clickable" alkynyl benziodoxolone bearing an azide group.T his reaction proceeds fast, under mild physiological conditions,and with avery high degree of chemoselectivity.T he formed azide-capped alkynyl-cysteine adducts are readily detectable by LC-MS/MS, and can be further functionalizedw ith TAMRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Contrary to AspA controls, 12 , 13 the removal of thiols on cell surfaces with maleimide 26 , 22 iodoacetamide 27 , 12 and the most powerful hypervalent iodine reagent 28 ( 29 ) failed to inactivate ETP 6 ( Figure 4 C). Similarly, the presence of 10% serum 22 caused only a minor ∼25% reduction of ETP uptake ( Figures 4 C and S5 ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Contrary to AspA controls, 12 , 13 the removal of thiols on cell surfaces with maleimide 26 , 22 iodoacetamide 27 , 12 and the most powerful hypervalent iodine reagent 28 ( 29 ) failed to inactivate ETP 6 ( Figure 4 C). Similarly, the presence of 10% serum 22 caused only a minor ∼25% reduction of ETP uptake ( Figures 4 C and S5 ).…”
Section: Resultsmentioning
confidence: 91%
“…This poor responsiveness to inhibitors and activators such as cytochalasin B, DTT, Ellman’s reagent, TFRC siRNA, or serum indicated that the unique reactivity of ETPs is decisive for function. High reactivity of ETPs in both oxidized and reduced form allows for covalent capture by nonactivated thiols and disulfides in cellular targets 29 that are otherwise beyond reach ( Table 1 , entries a–d, f, h–i). Moreover, the possibility of repeated disulfide-exchange cycles in neutral water suggested that ETPs can change targets during uptake ( Table 1 , entries a–d, e–g).…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Adibekian, Waser,a nd co-workers reported an efficient method for the proteomic profiling of cysteine residues in complex proteomes in both cell lysates and living cells by using azide-functionalized alkynyl benziodoxolone 100 (Scheme 20). [51] Theobtained thioalkyne adducts could be easily functionalized by copper-catalyzed cycloaddition of the azide with alkynes (CuAAC), either with fluorophores or biotin. Benziodoxolone 100 (JW-RF-010) was both more efficient and more selective than state-of-the-art reagents for cysteine functionalization, such as N-iodoacetamides,a nd allowed the identification of ad ifferent set of proteins.T he method was used for the identification of the targets of curcumin in HeLa cells.…”
Section: Reviewsmentioning
confidence: 99%
“…Michael additions to α,β-unsaturated carbonyl compounds in maleimides,6 sulfone reagents7 and recently developed carbonylacrylic reagents8 are the most prominent examples. Other methods rely on SN 2 -reactions of haloalkyl bonds such as iodoacetamides,9 on alkynylation10 and fluoroalkylation11 with hypervalent iodine reagents, on nucleophilic aromatic substitution of perfluoroaromatic compounds12 or on Pd-mediated cross-coupling 13. The level of reactivity for cysteine in these methods is predetermined by the chemical nature of the reactive group itself.…”
Section: Introductionmentioning
confidence: 99%